Do graduate entry nursing student's experience 'Imposter Phenomenon'?: An issue for debate. (July 2016) - Aubeeluck, Aimee; Stacey, Gemma; Stupple, Edward J.N.
Abstract: The recruitment of Graduates into the nursing profession is seen as advantageous in the academic literature. Conversely educated nurses are often portrayed in the media as "too posh to wash". We would argue these conflicting discourses have a negative effect on graduate entry nurse education. Graduate nursing students may be particularly susceptible to "Imposter Phenomenon" a concept that describes an "internal experience of intellectual phoniness" exhibited by individuals who appear successful to others, but internally feel incompetent. We would like to encourage debate through the presentation of a small set of pilot data that established that 70% of the participants had frequent to intense experiences of Imposter Phenomenon. Students experienced feelings of failure despite consistent high achievement. Our findings and the prevalent negative rhetoric surrounding highly educated student nurses raise concerns regarding the impact of the anti-intellectualism on the Graduate entry student's perception of self. Others may argue that this could simply be a 'natural' or expected level of anxiety in a time of transition that has no lasting impact. We debate this issue in relation to the existing literature to encourage critical dialogue. Highlights: We argue that 'Imposter Phenomenon' is experienced by many student nurses. We discuss the role of an anti-intellectualism culture in breeding feelings of failure. We encourage critical dialogue of the student experience in nurse education.